“Changing the narrative”: a study on professional identity formation among Black/African American physicians in the U.S - Wyatt, Tasha R.; Rockich-Winston, Nicole; White, DeJuan; Taylor, Taryn R. (Advances in health sciences education : theory and practice, 2021)
Professional identity formation (PIF) is considered a key process in physician development. However, early PIF research may have inadvertently left out experiences from ethnically/racially minoritized physicians. As a result, the PIF literature may have forwarded dominant perspectives and assumptions about PIF that does not reflect those of minoritized physicians. This study used a cross-sectional study design, in which interview data was initially collected using constructivist grounded theory and then analyzed using critical lenses. Participants included 14 Black/African American students, 10 residents, and 17 attending physicians at two Southern medical schools in the U.S. Coding included the both/and conceptual framework developed out of Black feminist scholarship, and further analyzed using medicine’s culture of Whiteness. These lenses identified assumptions made in the dominant PIF literature and how they compared to the experiences described by Black physicians. The results show that medical education’s historical exclusion of minoritized physicians in medical education afforded a culture of Whiteness to proliferate, an influence that continues to frame the PIF research. Black physicians described their professional identity in terms of being in service to their racial/ethnic community, and the interconnectedness between personal/professional identities and context. Their professional identity was used to challenge larger social, historical, and cultural mistreatment of Black Americans, findings not described in the dominant PIF research. Black physicians’ experiences as minoritized individuals within a culture of Whiteness reveals that the PIF literature is limited, and the current framings of PIF may be inadequate to study minoritized physicians.